PELATIHAN PEMBUATAN RUNNING TEXT UNTUK TAMPILAN INFORMASI DI DESA DUWET KECAMATAN TUMPANG - Agus Pracoyo; Leonardo Kamajaya; Subiyantoro Subiyantoro; Donny Radianto; Yulianto Yulianto (P3M Politeknik Negeri Malang, 2021)
The use of running text as a promotional media is considered very effective and can bring many benefits to a business. In Duwet Village, there is a UMK that produce several superior products, including corn rice (gerit), cassava crackers and bamboo crafts (besek). UMK in Duwet village require media that can be used for marketing media. This underlies the PkM team to conduct training in making running texts. The target in this training is the youth group of Duwet Village. The results of this dedication, it is hoped to be able to socialize and market superior products when guests or foreigner visits Duwet Village.